Labeling on Molecular Graph inducing Topological Indices - J. Gowri; J. Jayapriya (The Bioscan, 2025)
Graph labeling is the assignment of integers to vertices or edges or both under certain conditions. In this article, we link graph label-ing and topological indices as concepts. We introduce topological indices in particular for specific molecular graphs that permit HMC labeling. The concept of graphs is playing a significant role in the examination of QSPR data using topological indices. This part considers the labeled square index SQI(G), labeled product index PI(G), labeled sum index SI(G), labeled Nirmala index NI(G), labeled Sombor index SOLI(G), labeled forgotten index FI(G), and the grouping of all these indices. These topological indices corre-late certain physic-chemical properties such as polar surface, Polarizability, molar volume, and boiling point.